Stress corrosion cracking of nuclear grade steels - Gammon, M A (Centre for Materials Engineering, 2016)
A nuclear grade 316L stainless steel and a 508-111 quenched and tempered pressure vessel steel were studied for their stress corrosion cracking susceptibility. Cylindrical tensile specimens were subjected to slow strain rate testing at 75°C in aerated, aqueous solutions (distiled water with 1000ppm Cl⁻ or SO₄ = ions in solution) in a range of corrosion potentials. The 316L has been examined for sensitization and stress corrosion resistance. This study has shown that the peak degree of sensitization attainable in this material is well within the limits considered as safe by the nuclear power industry. This material is not susceptible to environmentally assisted cracking as long as the potential is kept below the pitting potential for the material. A single instance of intergranular stress corrosion cracking was noted when this material was tested in 1000ppm Cl⁻ solution at 440mV (SHE). Two casts of 508-111 have been examined: 508-A has been tested in the as quenched condition as well as after two tempering heat treatments, while 508-B has been tested in the fully tempered condition only. The mechanical properties of the 508 type materials are strongly influenced by the heat treated condition and mildly influenced by the service environment. In the quenched condition anodic intergranular stress corrosion cracking is severe in the chloride solution and it is argued that the absence of intergranular cracking in the sulphate solution is due to the over aggressiveness of this environment. In all three heat treated conditions loss of ductility is more pronounced in sulphate solutions than in chlorides. Transgranular cleavage is evident in strongly cathodic conditions and this is ascribed to the ingress of hydrogen. The transgranular hydrogen embrittlement seems to be independant of heat treated condition. Rising load tests on fatigue precracked specimens have indicated that environmentally enhanced crack growth of existing defects does not occur for the conditions tested.